Germinal peptide eye drops promote corneal wound healing and decrease inflammation after alkali injury. (October 2020) - Guan, Jieying; Zhou, Lijia; Wang, Li; Li, Xiaoyi; Pan, Zhiqiang
Abstract: Germinal peptide is being developed to treat corneal injuries. The purpose of this study was to investigate its effect on corneal epithelial cells in vitro and its ability to promote healing in an alkali injury model in vivo . Cultured rabbit corneal epithelial cells were treated with germinal peptide at three concentrations. Cell proliferation and migration were assessed and compared with the effect of recombinant human epidermal growth factor (rh-EGF). In vivo, the corneas of New Zealand albino rabbits were chemically burned with 1 mol/l NaOH for 30 s. The injured eyes were topically treated with germinal peptide (10, 20, and 40 μg/ml), rh-EGF, or phosphate-buffered saline thrice daily. At fixed time points post injury, the healing of the cornea and its histopathology were evaluated. There was no difference in the effect of germinal peptide on cultured cell proliferation. However, cell migration was significantly higher than that in the control groups, with germinal peptide at concentrations of 20 and 40 μg/ml being the most efficacious. In vivo, 20 and 40 μg/ml germinal peptide significantly alleviated corneal opacity and edema. By day 21, the areas of corneal neovascularization in the germinal peptide-treated groups were smaller than those in the rh-EGF and control groups. The repaired corneas in the germinal peptide- and rh-EGF-treated groups also had more corneal epithelial layers and fewer inflammatory cells than the controls. Germinal peptide may be developed as a novel topical treatment agent for corneal wound healing in clinical settings. Highlights: We studied the effect of germinal peptide (GP) on healing of alkali eye damage. Twenty and 40 μg/ml GP significantly alleviated corneal opacity and edema. At 21 d, corneal neovascularization, epithelial layers, and inflammation were lower. GP increased rabbit corneal epithelial cell migration in vitro . GP may provide a novel topical approach to corneal wound healing in the clinic.